simplify (2.01)(-2x)(-5x)


Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

simplify (2.01)(-2x)(-5x)

I can't figure out how to simplify this variable expression: (2.01)(-2x)(-5x)

Research, Knowledge and Information :



Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

Simplify (x – 1)(x2+ 5x + 2) - OpenStudy


... x^3 + 5x^2 + 2x - x^2 - 5x - 2 x^3 + 5x^2 - 1x^2 + 2x - 5x - 2 x^3 + 4x^2 - 3x - 2 ... (5x) +x(2) + (-1)(x^2) + (-1)(5x) + (-1)(2) simplify and combine like terms
Read More At : openstudy.com...

Simplify 2x+5x - YouTube


Jul 07, 2013 · Simplify 2x+5x TacomaCCMath. Loading... Unsubscribe from TacomaCCMath? ... 01. Simplify 3y+5x-2y-2x+1 - Duration: 1:18. TacomaCCMath 2,197 views.

Simplify 5x – 3{2x – 2[x – 2(1 - Brainwire


Find the product √5x4y √10xy3 3. ((9+3x)/(x+1))/((9-x^2)/(x^2-1)) 4. Simplify the expression -3(4x – 2) – 2(5x ... Simplify 5x – 3{2x – 2[x – 2(1 – x ...
Read More At : www.brainwire.co...

Simplify: (4x^2-1)/(2x^2+5x-3)? - Weknowtheanswer


Solution for 2x^2+7x+3=0 equation: Simplifying 2x 2 + 7x + 3 = 0 Reorder the terms: 3 + 7x + 2x 2 = 0 Solving 3 + 7x + 2x 2 = 0 Solving for variable 'x'.
Read More At : www.weknowtheanswer.com...

Simplify 3x + 6x 2 - 5x - x 2. 6x 2 + 2x 6x 2 - 2x 5x 2 - 2x ...


Simplify 3x + 6x 2 - 5x - x 2. - 913370. 1. ... Simplify 3x + 6x 2 - 5x - x 2. 6x 2 + 2x 6x 2 ... 2016-01-24T23:26:59-05:00. A1: ...
Read More At : brainly.com...

Simplify 5x 3{2x 2[x 2(1 x)]} - Sell Downloads - dgoodz


... {2x 2[x 2(1 x)]} Find the product ?5x4y ?10xy3 ((9+3x)/(x+1))/((9-x^2)/(x^2-1)) Simplify the expression ... Simplify 5x 3{2x 2[x 2(1 ... (Updated 1/01 /2016 ...
Read More At : www.dgoodz.com...

Simplify 3(2x^2-1) - (5x^2+x+3)? - Weknowtheanswer


Simplify 3(2x^2-1) - (5x^2+x+3)? ... Answer #1 | 10/10 2014 01:57 3(2x²-1) - (5x²+x+3) ... SOLUTION: Simplify x^4-5x^2+4 - Algebra. Read more. Positive: ...
Read More At : www.weknowtheanswer.com...

simplify 2(5x -y)-3(3x-y) - Brainly.com


simplify 2(5x -y)-3(3x-y) - 2625382. 1. Log in Join now ... by shammy161 01/16/2017. Log in to add a comment ... mPN = 2x - 16 Find angle X ...
Read More At : brainly.com...

Suggested Questions And Answer :



Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

sqrt(3a+10) = sqrt(2a-1) + 2

sqrt(3a+10)=sqrt(2a-1)+2 To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(3a+10))^(2)=(~(2a-1)+2)^(2) Simplify the left-hand side of the equation. 3a+10=(~(2a-1)+2)^(2) Squaring an expression is the same as multiplying the expression by itself 2 t
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Fac
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

(13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

(8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

what is the answer for x/7+4=x/7

(x)/(7)+4=(x)/(7) Multiply each term in the equation by 7. (x)/(7)*7+4*7=(x)/(7)*7 Simplify the left-hand side of the equation by canceling the common terms. x+28=(x)/(7)*7 Simplify the right-hand side of the equation by simplifying each term. x+28=x Since x contains the variable to solve for, m
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Write out the solution to the equation : x + y - z = 0, 2x + 4y - z = 0 and 3x + 2y + 2z = 0

first equation: x + y - z = 0 x + y = z in the other 2 equations, replace z with x + y: 2x + 4y -(x+y) = 0 3x + 2y +2(x+y) = 0 simplify: 2x + 4y -x -y = 0 3x + 2y +2x +2y = 0 simplify more: x + 3y = 0 5x + 4y = 0 in the top equation, move the 3y to the other side: x = -3y in the bottom
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

find a particular solution (e^x+y +ye^y)dx+(xe^y -1)dy=0 if y(0)=-1

This has the form of an exact DE. Let's see if it is.  First rewrite: (e^x+y+ye^y)+(xe^y-1)dy/dx=0=A(x,y)+B(x,y)dy/dx=0 where A=e^x+y+ye^y and B=xe^y-1. (p.d.=partially differentiate; wrt=with respect to)   Take A and p.d. wrt y=1+ye^y+e^y (a) Take B and p.d wrt x=e^y (b) S
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

simplify 6x/x+3=9/x-3-15/x^2-9

  6x / (x + 3) = [9 / (x - 3)] - [15 / (x^2 - 9)] 6x(x - 3) / (x + 3)(x - 3) = [9(x + 3) / (x + 3)(x - 3)] - [15 / (x^2 - 9)] (6x^2 - 18x) / (x^2 - 9) = [(9x + 27) / (x^2 - 9)] - [15 / (x^2 - 9)] 6x^2 - 18x = 9x + 27 - 15 6x^2 - 18x - 9x - 12 = 0 6x^2 - 27x - 12 = 0
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how would you simplify this expression (1/y)+(2/7)-(3/2y^2)

(1/y) +(2/7) -(3/2y^2)=0 multipli bi y^2...y +(2/7)y^2 -(3/2)=0 or 14*(2/7)y^2 +14y -14*(3/2)=0 4y^2 +14y -21=0 or (x-1.1331406)(x+4.6331406)=0
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1078 seconds